Traditional Art and Cultural Inheritance as Dynamic Development of Gandrung Performing Art - traditional art; Hasan, Moh.; Macaryus, Sudartomo; Imawati, Endah; Saddhono, Kundharu; Sungkowati, Yulitin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to to formulate a model of inheritance and development of Gandrung as Banyuwangi traditional arts performances. By using ethnographic methods, data from published sources include field data obtained through observation, participation and in-depth interviews with selected respondents, namely artists, community and cultural leaders at Banywuangi. Semiotic interpretation of data is done by treating each phenomenon as a cultural phenomenon that related one another. The results shows that the inheritance and development takes place through regulation of Gandrung by setting Gandrung as Banyuwangi tourism mascot. Gandrung undergoes metamorphosis of art into art of social struggle and eventually evolved into entertainment art. The metamorphosis begins with the turn of Gandrung male dancer to be Gandrung female dancer. These events leave a pullback legend of GandrungMarsan and emergence as the first woman of Gandrung. The figures in the cessation of Marsan as a male dancer (Lanang) still leave tradition until 1956, with the presence of Hamlet GumukGandrung at GumukLor, Licin district, Banyuwangi. The stigma occurs because of the strong teaching of religious belief. Thus, the inheritance and other development took place through training, collaborative performances, festivals, cultural ambassador, diversification of performances and creative industry products